Edukacja demokratyczna a kreatywność - Michałowska, Danuta A. (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
In democratic education should be used special forms and methods of teaching and learning. One of such method is drama, which stimulates creativity and self-expression. The results of the research showed, that drama is an effective teaching and learning method by experience, because it stimulates both the cognitive and affective development. Moreover, teaching through drama helps young people to become receptive to values and to shape their own system of values. Drama with elements of the psychodrama can be simultaneously applied as the method of the democratic education and as the method of upbringing in ethical and philosophical development.